Influence of transparency on the organizational management of the Regional Government of Tacna, period 2011 – 2014 - Rodas Alejo, Pedro Casiano (2019)
The present work of investigation has as principal aim determine the influence of the transparency in the management organizacional of the Regional Government of Tacna during the period 2011 - 2014; it was considered to be a sample of 266 persons; the type of investigation was basic of level correlacional, being the not experimental design; one thought that significant influence of the perception exists on the transparency in the management organizational that it characterizes to the entity. One found that the level of trasparencia that it perceives the electoral population of Tacna on his Regional Government is regular, and that the dimension "Investigation and sanction" was the most out-standing, and the focused one to improving the "Institucionality and efficiency"; the level of management organizational that is perceived is inadequate, being the most out-standing dimension the "Development organizational", and the focused one to improving the "Democratic Gobernability".